Determining the Thermodynamic Properties of Fuel Blends from those of their Components For Air-Fuel Models of IC Engines (University of Khartoum Engineering Journal, 2022)
The paper presents an Excel-based procedure for determining the coefficients in the polynomials thatdescribe the thermodynamic properties of fuel blends. The procedure is meant for use in conjunction with air-fuelcomputer models of internal combustion engines. It enables such models to deal with fuel blends just as they dealwith pure fuels without modifying the main computer program. To obtain the mixture properties, the procedureapplies the ideal-gas mixture relationship, which is already inherent in the formulation of existing air-fuels models.Excel has been chosen as computational platform for developing the procedure because of its simplicity and wideavailability. The procedure is applied to determine the coefficients for binary mixtures of gasoline-ethanol,gasoline-hydrogen, and methane-hydrogen